1999
DOI: 10.1016/s0893-133x(99)00028-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Dorsomedial Hypothalamus in Mediating the Response to Benzodiazepines on Trial 2 in the Elevated Plus-Maze Test of Anxiety

Abstract: Trial 2 in the elevated plus-maze provides an animal model of specific phobia (fear of heights). On this trial

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 46 publications
1
14
0
2
Order By: Relevance
“…At the highest dose (10.0 mg/kg), however, the WAY 161503-induced changes in open arm exploration and risk-assessment were accompanied by a robust hypolocomotion as indicated by reduction in the absolute number of closed-arm entries. As a whole these results further corroborate previously reported studies showing selective, preferential and non-selective 5-HT 2C agonists to exhibit anxiogeniclike properties and locomotor impairments (Kennett et al 1989;Rodgers et al 1992;Grewal et al 1997;Mora et al 1997;Olivier et al 1998;Setem et al 1999;Bagdy et Repeated EPM exposures are known to reduce or abolish the anxiolytic-like effects of benzodiazepines, a phenomenon known as "one-trail tolerance" or acute tolerance in this test (File, 1990;File, 1993;File, Zangrossi, Viana, & Graeff, 1993;File, Gonzalez, & Gallant, 1999;Frussa-Filho & Ribeiro, 2002;Vargas, Da Cunha, & Andreatini, 2006;Albrechet-Souza, Borelli, & Brandão, 2008). Our present results with the 5-HT 2C agonist WAY 161503 showed that both the first and second EPM exposures were similarly able to detect anxiogenic-like effects.…”
Section: Discussionsupporting
confidence: 91%
“…At the highest dose (10.0 mg/kg), however, the WAY 161503-induced changes in open arm exploration and risk-assessment were accompanied by a robust hypolocomotion as indicated by reduction in the absolute number of closed-arm entries. As a whole these results further corroborate previously reported studies showing selective, preferential and non-selective 5-HT 2C agonists to exhibit anxiogeniclike properties and locomotor impairments (Kennett et al 1989;Rodgers et al 1992;Grewal et al 1997;Mora et al 1997;Olivier et al 1998;Setem et al 1999;Bagdy et Repeated EPM exposures are known to reduce or abolish the anxiolytic-like effects of benzodiazepines, a phenomenon known as "one-trail tolerance" or acute tolerance in this test (File, 1990;File, 1993;File, Zangrossi, Viana, & Graeff, 1993;File, Gonzalez, & Gallant, 1999;Frussa-Filho & Ribeiro, 2002;Vargas, Da Cunha, & Andreatini, 2006;Albrechet-Souza, Borelli, & Brandão, 2008). Our present results with the 5-HT 2C agonist WAY 161503 showed that both the first and second EPM exposures were similarly able to detect anxiogenic-like effects.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, in our confirmatory factor analysis study of na CD-1 mouse behaviour in the elevated plus-maze (n=200), open entries, open time ratio, unprotected head dips and unprotected stretch attends were reduced by approximately 50% in trial 2 (Wall and Messier 2000b). In contrast to these between-trial behavioural response differences, indicating some form of learning during trial 1 (Espejo 1997;File et al 1998File et al , 1999File et al , 2000Holmes and Rodgers 1998;Kenny et al 2000;Ouagazzal et al 1999), there were some noticeable increases between the trial 1 (drug injection) and trial 2 (no drug injection) unprotected exploration measures in experiment 1. Whereas the vehicle group showed lower trial 2 unprotected exploration activity levels, the 5-and 20-nmol groups actually showed some higher trial 2 unprotected exploration activity levels (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…EPM apparatus consists of two opposite open arms 50 × 10 cm and two opposite arms enclosed by 40 cm high walls and elevated 50 cm from the floor. The arms are connected by a central 10 × 10 cm square, and thus the maze forms a "plus" shape (File et al, 1999).…”
Section: Elevated Plus-maze (Epm)mentioning
confidence: 99%